Analysis for ground anchor using 2D simulation model by MIDAS/GTS software - MUNIRA SUNGKAR; JASON WU (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
Ground anchors are commonly exposed to both acidic and alkaline ground conditions depending on ground mineral content, soil/rock type, age and groundwater flow path. It is essential to understand the limitations to ground anchorage materials especially when exposed to aggressive ground conditions whilst in a stressed state. This study discusses about ground anchors and analysis of the ground anchor failure trigger by corrosion, which analysed by using difference software in previous study (ABAQUS) compare with simulation model analysed by 2D Midas/GTS. Numerical techniques may be very efficient for investigating the load transfer of ground anchors. The results of anchor failures in numerical modeling are different from previous study (field test results), practiced by first cement crack and then wire break. Recommendations are given for applying FEM (finite element method) analysis to the design of anchored stabilization systems, and also for analyzing design variables, and design loads, to achieve more efficient and cost-effective anchored stabilization systems. Several models or simulations are presented to illustrate the displacement and the load that applied to the anchor which analyzed by Midas/GTS software. However, the condition that the numbers of occurrence correspond to load of failures at the time of damages is caused as the consequence of material and model deviation